2011
DOI: 10.5897/ajmr11.575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various medicinal plant essential oils obtained from semi-arid climate on rumen fermentation characteristics of a high forage diet using in vitro batch culture

Abstract: Eighteen natural medicinal plant essential oils and garlic oil obtained from semi-arid climate were conducted to evaluate their effects on in vitro rumen microbial fermentation and their effectiveness for decrease in vitro ruminal methane production. 50 ml of buffered rumen fluid (1:2; rumen fluid: buffer solution) were introduced in 125 ml serum bottles containing 500 mg of 80:20 alfalfa hay to concentrate as basal diet and or basal diet plus 1 µ/ml of medium of medicinal essential oils or garlic oil (6 repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…Similar to the current experiment, it was observed that O. basilicum decreased DMD along with GP (DM incubated basis) of a 80:20 alfalfa hay:concentrate diet at 1000 mg L −1 . A previous report indicated that O. basilicum exhibited antimicrobial activity against a wide range of Gram‐positive and Gram‐negative bacteria due its high content of estragole, corroborating the reduction in digestibility observed in the present experiment.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Similar to the current experiment, it was observed that O. basilicum decreased DMD along with GP (DM incubated basis) of a 80:20 alfalfa hay:concentrate diet at 1000 mg L −1 . A previous report indicated that O. basilicum exhibited antimicrobial activity against a wide range of Gram‐positive and Gram‐negative bacteria due its high content of estragole, corroborating the reduction in digestibility observed in the present experiment.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with effects exhibited by C. aurantifolia in the present study, others reported that Citrus limon (1000 mg L −1 ), C. reticulata (333–1000 μL L −1 ) and C. sinensis (200–1200 mg L −1 ) contain chiefly limonene and decreased DMD and GP (DM incubated basis) from a range of dietary substrates . In an in vitro study, limonene was found to be responsible for the effects of C. reticulata on rumen microbial activity.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations